Influence of the Application of Various Preparations on the Quality of Melon Fruits (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article examines the influence of various preparations used for pre-sowing treatment of melon seeds and plant spraying during the growing season on the chemical composition of the fruits. Research results demonstrated that treating melon seeds before sowing with a water-soluble Nanosilicon concentrate (0.1 g/l) and Maxim XL 3.5% (5 ml/kg) at the recommended rate, as well as spraying plants with an iron oxide solution (Fe2O3-1 g/l) before flowering, positively affects the content of water-soluble dry matter, sugars, ascorbic acid, and nitrates in the fruits.